A maturing market : the Iberian book world in the first half of the seventeenth century - Wilkinson, Alexander S., 1975-; Ulla Lorenzo, Alejandra (Leiden ; Boston : Brill, 2017)
Within just a generation or two of its arrival, print had become a ubiquitous and spirited part of Spain and Portugal's urban cultures. It serviced an ever-expanding reading public, as well as many and varied practical quotidian needs. Its impact on society was multi-dimensional and complex, and its social reach far broader than the civic or ecclesiastical elites were ever to be entirely comfortable with. This cross-disciplinary volume of essays focuses on the maturing marketplace for print in the first half of the seventeenth century, shedding new light on some important transformations, with authors and publishers seizing opportunities available to them - negotiating the regulatory efforts of the censors, and scrambling to reconfigure their relationship with their readers.
Part 1. Surveys of the book trade -- A maturing market : the Iberian book world in the first half of the seventeenth century / Alexander S. Wilkinson -- Printing in Antwerp in the early seventeenth century and its connections with the Iberian world / César Manrique Figueroa -- The importation of books into New Spain during the seventeenth century / Idalia García -- Women and the Iberian book trade, 1472-1650 / Alejandra Ulla Lorenzo -- Part 2. Addressing the reader in golden-age Spain -- The book-reader relationship in golden-age Spain : reading practices and the publishing industry in Don Quixote / Sarah Malfatti -- 'Reasons of state for any author' : common sense, translation, and the international republic of letters / José María Pérez Fernández -- Writing literature for publication, 1605-1637 / Esther Villegas de la Torre -- Part 3. The stage in print -- Printed plays in early modern Spain / Don Cruickshank -- Cervantes's Ocho comedias : from the pen to the print-shop / John O'Neill -- Printing licenses and the trade in fiction in Spain in the first half of the seventeenth century / Manuel Calderón Calderón -- Part 4. Market specialisms : chivalric literature, medicine and the news -- Printing books of chivalry in Portugal at the beginning of the seventeenth century / Aurelio Vargas Díaz-Toledo -- Medical publishing in Portugal in the first half of the seventeenth century : a good business? / Hervé Baudry -- The golden age of the single event printed newsletter : relaciones de sucesos, 1601-1650 / Henry Ettinghausen -- 'Things worthy of being known' : the reception and consumption of the press in Catalonia during the first half of the seventeenth century / Ricard Expósito Amagat.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Book industries and trade -- Spain -- History -- 17th century; Book industries and trade -- Portugal -- History -- 17th century; Books and reading -- Spain -- History -- 17th century; Books and reading -- Portugal -- History -- 17th century; Publishers and publishing -- Spain -- History -- 17th century; Publishers and publishing -- Portugal -- History -- 17th century; Authors and publishers -- Spain -- History -- 17th century; Authors and publishers -- Portugal -- History -- 17th century; Livres -- Industrie -- Espagne -- Histoire -- 17e siècle.; Livres -- Industrie -- Portugal -- Histoire -- 17e siècle.; Livres et lecture -- Espagne -- Histoire -- 17e siècle.; Livres et lecture -- Portugal -- Histoire -- 17e siècle.; Écrivains et éditeurs -- Espagne -- Histoire -- 17e siècle.; Écrivains et éditeurs -- Portugal -- Histoire -- 17e siècle.; BUSINESS & ECONOMICS -- Commerce; BUSINESS & ECONOMICS -- Marketing -- General; BUSINESS & ECONOMICS -- Sales & Selling -- General; Authors and publishers; Book industries and trade; Books and reading; Publishers and publishing; Portugal; Spain; 1600-1699; History